Celebrating India’s dairy success on the country’s 75th independence anniversary - International Livestock Research Institute (2022)
ILRI produced this short (3-minute) photofilm in February 2022 to celebrate India’s 75th independence anniversary. The photofilm was part of a slide presentation ILRI Director General Jimmy Smith made for the Indian Council of Agricultural Research (ICAR) on 17 February 2022. Smith’s presentation was one of 75 lectures the Government of India organized from 12 March 2021 to 15 August 2022 as part of a 75-week countdown to commemorate India’s independence.